Answer:
each tick is 3.50
Step-by-step explanation:
14/4=3.5
hope dis helps \_)0___0)_/
Changing the coefficient of x to 6 changes the meaning of the expression as 5 is added to 6 times x
Solution:
Given that number 2 in the expression 5 + 2x is called the coefficient of x
We are asked to find what happens when changing the coefficient to 6 changes the meaning of the expression
In the expression,
5 + 2x
This means 5 is added to 2 times x or 5 is added to twice of x
Number 2 is called the coefficient of x
When we change this coefficient to 6, the expression becomes,
5 + 6x
So now the meaning of expression becomes,
5 is added to 6 times x
So changing the coefficient of x changes the meaning of the expression
Answer: Choice D) ![2\sqrt{5}](https://tex.z-dn.net/?f=2%5Csqrt%7B5%7D)
===========================================================
Work Shown:
Point A starts at (-2,3) and moves to (2,5) after applying the translation rule of "shift 4 to the right, 2 up".
Use the distance formula to find the distance from (-2,3) to (2,5)
![d = \sqrt{(x_1 - x_2)^2 + (y_1 - y_2)^2}\\\\d = \sqrt{(-2-2)^2 + (3-5)^2}\\\\d = \sqrt{(-4)^2 + (-2)^2}\\\\d = \sqrt{16 + 4}\\\\d = \sqrt{20}\\\\d = \sqrt{4*5}\\\\d = \sqrt{4}*\sqrt{5}\\\\d = 2\sqrt{5}\\\\d \approx 4.472136\\\\](https://tex.z-dn.net/?f=d%20%3D%20%5Csqrt%7B%28x_1%20-%20x_2%29%5E2%20%2B%20%28y_1%20-%20y_2%29%5E2%7D%5C%5C%5C%5Cd%20%3D%20%5Csqrt%7B%28-2-2%29%5E2%20%2B%20%283-5%29%5E2%7D%5C%5C%5C%5Cd%20%3D%20%5Csqrt%7B%28-4%29%5E2%20%2B%20%28-2%29%5E2%7D%5C%5C%5C%5Cd%20%3D%20%5Csqrt%7B16%20%2B%204%7D%5C%5C%5C%5Cd%20%3D%20%5Csqrt%7B20%7D%5C%5C%5C%5Cd%20%3D%20%5Csqrt%7B4%2A5%7D%5C%5C%5C%5Cd%20%3D%20%5Csqrt%7B4%7D%2A%5Csqrt%7B5%7D%5C%5C%5C%5Cd%20%3D%202%5Csqrt%7B5%7D%5C%5C%5C%5Cd%20%5Capprox%204.472136%5C%5C%5C%5C)
Answer:
20
Step-by-step explanation:
Answer:
i think b
Step-by-step explanation:
(2,2). When x of the line is 2, y of the line must be 2.
(-2,-2). When x of the line is -2, y of the line must be -2.
(2,2). y=mx+b or 2=1 × 2+b, or solving for b: b=2-(1)(2). b=0.
(-2,-2). y=mx+b or -2=1 × -2+b, or solving for b: b=-2-(1)(-2). b=0.
The equation of the line that passes through the points
(2,2) and (-2,-2)
is
y=1x
b came out to be zero, so there is no "+b" term.